The Effect of Taxation Compliance on the Financial Performance of Small and Medium Enterprises in Mukono District: A Case Study of Mukono Central Division - Esther Nasasira (Uganda Christian University, 2025)
This study centered on tax compliance and the financial performance of small and medium enterprises (SMEs) in Mukono District with a focus on Mukono Central Division. Specifically, the research evaluated the relationship between tax compliance and profitability, early tax filing and liquidity in business, and the effect of proper tax record keeping on financial stability. Descriptive cross-sectional study using quantitative approach was employed and 80 registered SMEs were the target from which 66 respondents were chosen using simple random sampling. Structured questionnaires were utilized to collect data, and descriptive statistics including means, percentages, and standard deviations with the assistance of SPSS software were used to analyze the data. The findings showed that tax compliance positively contributed to the financial performance of SMEs. Compliance with taxation laws and making timely payment of taxes were highly correlated with profitability since compliance did not attract any penalties and enhanced business reputation. Timely filing of taxes was found to ease liquidity through the maintenance of cash flow stability, prevention of unexpected expenses, and allowing for easier financial planning. Furthermore, improved record-keeping of taxations significantly contributed to fiscal sustainability through decision-making that is well-informed, reduced risk, and greater investor and lender confidence. The study identified tax compliance, prompt reporting, and maintaining proper records as the most important SME financial performance and sustainability determinants. Based on the findings, it is suggested that tax authorities and government institutions pursue continuous tax education programs, simplify filing procedures through technology-driven systems, provide selective incentives to SMEs, and increase the transparency of tax administration. Additionally, SMEs should adopt modern accounting systems and electronic equipment for improved precision in taxation records and to enable strategic financial management. Taken together, these actions can improve SME growth, profitability, and financial stability in the long run.
Undergraduate Thesis